AFFECTING FACTORS OF THE JAJANG AND RIMBA MAS FARMERS GROUP ACTIVITY IN GERBO VILLAGE - Liananta Azzahra; Latarus Fangohoi; Sutoyo Sutoyo (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
The farmer group has a function as a learning class, a vehicle for collaboration, and as a production unit (Permentan, 2016). Farmers' groups also play an important role in agricultural development, efforts to improve Human Resources (HR) in farmer groups can be done if farmers are active in farmer groups. Therefore, research was conducted on the factors that influence the activeness of the Jajang and Rimba Mas farmer groups. The research was conducted in Gerbo village, Purwodadi sub-district, Pasuruan Regency, East Java Province using descriptive quantitative methods. The population used was 77 people with 65 samples from the Jajang farmer group and the Rimba Mas farmer group. Data obtained from primary data obtained through questionnaires, interviews, and observations as well as secondary data obtained from the village government, BPP, sub-district offices, and others. The analysis used is descriptive and logistic regression analysis using SPSS software. The independent variables used were the level of education, land area, length of farming, leadership, the involvement of the extension agents, and the involvement of the village government. The dependent variable was the activity of the farmer groups. The results of the logistic regression analysis showed that the independent variables that had a significant effect on farmer group activeness were the land area and the involvement of extension workers.